From the LHC to IceCube, a melange of particle phenomenology - Talbert, R (2016)
Three topics in particle phenomenology are independently considered: (1) the flux of prompt atmospheric neutrinos at terrestrial observatories, (2) the resummation of dijet event shapes in Soft-Collinear Effective Theory, and (3) aspects of non-abelian discrete symmetries of flavour. The thesis thus decomposes into three chapters addressing each point in a self-contained way, including short introductions and concluding remarks. Regarding (1), we calculate the neutrino flux arising from the decay of charmed mesons produced in cosmic ray collisions in the atmosphere, with the charm cross-section being evaluated using NLO QCD techniques and input into a series of equations describing particle cascades. In (2) we present a NNLL' resummation of e+e− angularities, a class of observables generalizing thrust. This resummation necessarily includes the calculation of two-loop soft anomalous dimensions and matching corrections, which we also detail in generality. Finally, in (3), we develop a novel ‘bottom-up’ procedure to search for symmetries capable of predicting elements of fermionic mixing matrices and then apply it to both the quark and lepton sectors, finding numerous finite groups of interest.